2008
DOI: 10.1186/1754-9493-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the "FASTHUG" concept decreases the incidence of ventilator-associated pneumonia in a surgical intensive care unit

Abstract: Background: Ventilator-associated pneumonia (VAP) is a leading cause of morbidity and mortality in critically ill patients. The Institute for Healthcare Improvement 100,000 Lives Campaign made VAP a target of prevention and performance improvement. Additionally, the Joint Commission on Accreditation of Health Organizations' 2007 Disease Specific National Patient Safety Goals included the reduction of healthcare-associated infections. We report implementation of a performance improvement project that dramatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
(9 reference statements)
0
40
0
8
Order By: Relevance
“…Several of the studies reviewed employed additional elements (interventions) that were bundled with the original VCB (see Table 1). The VCB used by Papadimos et al (2008) was part of the FASTHUG bundle (Vincent, 2005) and included feeding assessment, blood glucose monitoring and pain assessment elements. The evidence for these additional elements is not based on research of patients who are mechanically ventilated and therefore they may not be suitable as VCB components.…”
Section: Bundle Elementsmentioning
confidence: 99%
“…Several of the studies reviewed employed additional elements (interventions) that were bundled with the original VCB (see Table 1). The VCB used by Papadimos et al (2008) was part of the FASTHUG bundle (Vincent, 2005) and included feeding assessment, blood glucose monitoring and pain assessment elements. The evidence for these additional elements is not based on research of patients who are mechanically ventilated and therefore they may not be suitable as VCB components.…”
Section: Bundle Elementsmentioning
confidence: 99%
“…In our project, we did not address the setting for application of the checklist. Published articles suggest that checklists can be used in several situations, including bedside rounds, 9,10,[12][13][14]103 as attachments to clinical pathways, 107 by individual clinicians, 13 and during shift-to-shift handover. 105 A limitation of our study is that the team members who used the NGT were volunteers from a single tertiary center; however, they were informed by international literature and followed an established and rigorous process to ensure systematic decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of this mnemonic in improving morbidity and mortality outcomes and communication has been demonstrated in a few studies. 13,14 When attempting to apply this checklist in the pediatric ICU (PICU), we found that FASTHUG has several inadequacies. Specifically, it does not support holistic pediatric care by incorporating the physiology and development requirements of children as indicated in the literature (eg, glucose control 15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been validated to improve at least the documentation of care processes. Individual units have developed their own variations of this critical care ''housekeeping'' to prevent nosocomial complications [32][33][34][35]. A culture of regular patient review is inexpensive and creates an environment where attention is focused on the patient in context rather than just management associated with the primary condition such as head injury or intracranial bleed.…”
mentioning
confidence: 99%